Analysis of Challenges of Enforcing International Humanitarian Law in the Asymmetric War in Aleppo - Wibowo, Rayhan Zaki; Azaria, Davilla Prawidya (Universitas Islam Sultan Agung, 2025)
This study aims to uncover the problems that arise in asymmetric warfare, which are different from the challenges in conventional warfare. The main focus of this study is the challenges of implementing International Humanitarian Law (IHL) in the context of asymmetric warfare, involving state and non-state actors. This study identifies the challenges in implementing IHL principles, such as the principles of distinction, proportionality, and humanity that are often violated. In addition, this study also highlights global political constraints, especially the veto power in the UN Security Council and the involvement of foreign countries, which hinder the enforcement of international law. The results of the study show that although the international legal framework has been established, its application in asymmetric warfare such as in Aleppo requires in-depth evaluation and strengthening of fairer and more independent accountability mechanisms.